PENGARUH PENERAPAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) TERHADAP KINERJA KARYAWAN PADA NPLTG-CNG JAKABARING (Studi Kasus Pada PT. Daruma Mitra Alam) - Rafita Sari; Yuliansyah M Diah; Kosasih Kosasih Kosasih Zen (JEMBATAN, 2016)
The purposes of this research is to determine the effect of the implementation of safety management systems and occupational health (SMK3) towards the performance of employees at the power plant-CNG Jakabaring (case study on PT. Daruma Mitra Alam) .PT. Darum Mitra Alam has a special department that handles about occupational safety and health (K3) called as HSE department (Health, Safety, Environment). To analyze the data, researchers used descriptive analysis containing any statements from each variable, then the simple linear regression analysis along with hypothesis testing. Simple regression result indicates that the value of R square is 0.191, thus SMK3 variables could explain the variable Employee Performance by 19.1%. Based on these results, we can conclude that SMK3 (X) has a positive and significant effect on employee performance (Y) on PT. Daruma Mitra Alam. Keywords: SMK3, Employee Performance, and HSE